2017
DOI: 10.1038/ejhg.2017.52
|View full text |Cite
|
Sign up to set email alerts
|

Variants in CPLX1 in two families with autosomal-recessive severe infantile myoclonic epilepsy and ID

Abstract: For a large number of individuals with intellectual disability (ID), the molecular basis of the disorder is still unknown. However, whole-exome sequencing (WES) is providing more and more insights into the genetic landscape of ID. In the present study, we performed trio-based WES in 311 patients with unsolved ID and additional clinical features, and identified homozygous CPLX1 variants in three patients with ID from two unrelated families. All displayed marked developmental delay and migrating myoclonic epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 12 publications
0
33
0
1
Order By: Relevance
“…This difference in configuration was also quantified by computing the distribution of peptide backbone dihedral angles for CPX-1 and mCpx1 as shown in Figures 7G – I . Notably, a point mutation in L128 (L128M) of the human mCpx1 ortholog has been identified in a patient with significant intellectual disability, severe seizures, myotonia, and conductive hearing loss ( Redler et al, 2017 ). In summary, MD simulations suggest that the final eight residues of mammalian complexin adopt a more structured configuration that promotes membrane binding despite the relatively low hydrophobicity of this region compared to nematode complexin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference in configuration was also quantified by computing the distribution of peptide backbone dihedral angles for CPX-1 and mCpx1 as shown in Figures 7G – I . Notably, a point mutation in L128 (L128M) of the human mCpx1 ortholog has been identified in a patient with significant intellectual disability, severe seizures, myotonia, and conductive hearing loss ( Redler et al, 2017 ). In summary, MD simulations suggest that the final eight residues of mammalian complexin adopt a more structured configuration that promotes membrane binding despite the relatively low hydrophobicity of this region compared to nematode complexin.…”
Section: Resultsmentioning
confidence: 99%
“…Complexin is a small (130–150 residue) cytoplasmic protein that binds directly to the assembled SNARE complex via a highly conserved alpha helical domain termed the central helix (CH) ( McMahon et al, 1995 ; Melia, 2007 ; Brose, 2008 ; Trimbuch and Rosenmund, 2016 ). Human complexin mutations ( CPLX1 gene) are associated with severe epilepsy, cortical atrophy, and intellectual disability ( Karaca et al, 2015 ; Redler et al, 2017 ). Loss-of-function studies in different model synapses revealed similarities as well as prominent differences in complexin function.…”
Section: Introductionmentioning
confidence: 99%
“…Missense; Nonsense (Corradi et al, 2014) Docking and priming Gburek-Augustat et al, 2016;Lammertse et al, 2020;O'Brien et al, 2019;Parrini, Marini, & Mei, 2017;Stamberger et al, 2016;Uddin, Woodbury-Smith, & Chan, 2017;Valence et al, 2019) CPLX1 (605,032) COMPLEXIN 1 3 0 AR Nonsense (Redler et al, 2017) RIMS1 (606,629) PROTEIN REGULATING SYNAPTIC MEMBRANE EXOCYTOSIS 1 2 0 AD, de novo Frameshift (Dong et al, 2014;Peter et al, 2019) RIMS3 ( (Salpietro, Lin, & Delle Vedove, 2017;Salpietro et al, 2019;Shen et al, 2017) STX1A ( (Jodice et al, 1997;Epi, 2016;Reinson et al, 2016;Romaniello et al, 2010;Tonelli et al, 2006;…”
Section: University Of Cambridge Neurodevelopmental Human Phenotypementioning
confidence: 99%
“…Although such expression level changes may not be causal in these disorders, they could contribute to their corresponding symptomatology (78). Recently, homozygous mutations in the complexin CTD have been identified through whole exome sequencing in patients with severe infantile myoclonic epilepsy and intellectual disability (79). Complexin-1 and -2 double knockout mice die shortly after birth, likely from deficits in synaptic transmission in multiple neuronal networks (42,80).…”
Section: Complexinmentioning
confidence: 99%